2016
DOI: 10.1073/pnas.1610631113
|View full text |Cite
|
Sign up to set email alerts
|

Extensive phosphorylation of AMPA receptors in neurons

Abstract: Regulation of AMPA receptor (AMPAR) function is a fundamental mechanism controlling synaptic strength during long-term potentiation/depression and homeostatic scaling. AMPAR function and membrane trafficking is controlled by protein-protein interactions, as well as by posttranslational modifications. Phosphorylation of the GluA1 AMPAR subunit at S845 and S831 play especially important roles during synaptic plasticity. Recent controversy has emerged regarding the extent to which GluA1 phosphorylation may contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 47 publications
7
84
2
Order By: Relevance
“…53 Our results also show that ketamine increases the phosphorylation of GluA1 at a protein kinase A site (Ser 845 ). Although phosphorylation of Ser 845 -GluA1 has a role in increasing channel conductance and insertion of AMPARs at the synapse, 44,45 we did not find a change in the basal properties of synaptic transmission in ketamine-treated mice. Several reports have demonstrated that ketamine, and also (2R,6R)-HNK, applied in the perfusion solution enhance AMPARmediated synaptic transmission in the hippocampus.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…53 Our results also show that ketamine increases the phosphorylation of GluA1 at a protein kinase A site (Ser 845 ). Although phosphorylation of Ser 845 -GluA1 has a role in increasing channel conductance and insertion of AMPARs at the synapse, 44,45 we did not find a change in the basal properties of synaptic transmission in ketamine-treated mice. Several reports have demonstrated that ketamine, and also (2R,6R)-HNK, applied in the perfusion solution enhance AMPARmediated synaptic transmission in the hippocampus.…”
Section: Discussioncontrasting
confidence: 70%
“…[44][45][46] Interestingly, chronic stress and administration of ketamine were found to modulate the phosphorylation of GluA1 in the hippocampus 5,38 and amygdala. 47 We therefore examined the possibility that a potential mechanism for LTP induction by HFS and inhibition by ketamine involved an altered phosphorylation of GluA1 in the NAc.…”
Section: 11mentioning
confidence: 99%
“…To determine whether the presence of NPC1 mRNA in synapses resulted in the local synthesis of the protein during LTP, this form of plasticity was chemically induced in synaptosomes by adding glycine and KCl in the absence of MgCl 2 [23,24]. The efficiency of the chemical LTP (cLTP) protocol in synaptosomes was confirmed by the phosphorylation of the AMPA receptor subunit GluA1 [25] (Appendix Fig S3). Consistent with local NPC1 translation, cLTP in wt synaptosomes induced a significant 82% increase in NPC1 levels, which was prevented by incubation with the protein synthesis inhibitor cycloheximide ( Fig 1G).…”
Section: Npc1 Is Present At the Synapses Where It Is Locally Translatmentioning
confidence: 99%
“…All sites have been implicated in receptor trafficking in the membrane[53]. At rest, S831 and S845 are phosphorylated in ~15% of receptors (on average, across all synapses, with unknown inter-synaptic variability)[56]. With LTP, phosphorylation of each can increase 2-fold[56], while LTD can result in loss of phosphorylation at S845[57-60] with no changes at S831[60].…”
Section: Multiple Factors Regulate Ampar Conductance In Hippocampusmentioning
confidence: 99%